Brain maturation changes characterized by algorithmic complexity (lempel and ziv complexity) - Fernández, J.G. (2007)
Recent experimental results suggest that basal electroencephalogram (EEG)changes reflect the widespread functional evolution in neuronal circuits, occurring in chicken brain during the "synapse maturation" period, between 3 and 8 weeks' posthatch. In present work a quantitative analysis based on the Algorithmic Complexity (Lempel and Ziv Complexity) is performed. It is shown that this complexity presents a peak at week 2 posthatch 2, and a tendency to stabilize its values after the week 5 posthatch. © 2007 American Institute of Physics.